Concept design 2 : works from seven Los Angeles entertainment designers and seventeen guest designers. - Belker, Harald, ....-; Burg, S., ....-; Clyne, J., ....- (Culver City : Designstudio, 2006)
Features the work of concept designers: Harald Belker, Steve Burg, James Clyne, Mark Goerner, Neville Page, Nick Pugh, Scott Robertson and guest artists: Nicholas Bouvier, Ryan Church, Dylan Cole, Kasra Farahani, Sean Hargreaves, Khang Le, Warren Manser, Stephan Martiniere, Ed Natividad, Rick O'Brien, Dan Wuarnstrom, Christian L. Scheuerer, Oliver Scholl, Farzad Varahramyan, Mike Yamada, Felix Yoon & Feng Zhu.